Assessment of the Philippine National Police (PNP) Human Rights Development Program (HRDP) in Protecting the Community from Abuse in Tabaco City, Albay, Philippines - Macabeo, Manny (JPAIR Multidisciplinary Research, 2022)
Enforcing the law serves as the key function of the police officer to maintain peace and order, thus, ensuring strict conformance with human rights. This study was conducted to assess the implementation of the PNP Human Rights Development Program in Tabaco City, Albay, Philippines, along with Institutional policy development, capability building on human rights protection, prevention and control measures on abuse of human rights, and strengthening of partnership and cooperation with multi-sectoral organizations for human rights compliance. It also identified the problems encountered and formulated an action plan that aims to further enhance the implementation of the program. The personnel assigned at the PNP Human Rights Development Program in Tabaco City selected Community Officials, and members of the community were the respondents of the study. Hence, the study revealed that the community and other partner stakeholders have understood and accepted the principles of the programs implemented. Therefore, the primary objectives of the PNP in gaining the trust and confidence of the community were achieved. The study recommends the sustainability of the program through inculcating greater social responsibility, intervening appropriately, and acquiring useful and timely information for implementation of anti-human rights abuse programs which shall be continuously participated by the community with enhanced multi-sectoral collaboration to achieve a safer community free from abuse.
Keywords: Social Science; human rights development program; Philippine National Police; protection; descriptive; Tabaco City; Philippines